Sosialisasi dan Pelatihan Pengolahan Pisang Crispy dan Selai Kopi di Simpang Kandis, Kelurahan Sumber Jaya Kota Bengkulu - Syahputra, Yudian; Wulandari, Suci Rahma; Puspita, Beni; Widawati, Lina; Andriani, Evi (Universitas Dehasen Bengkulu, 2023)
Simpang Kandis especially RT 17 RW 01 has 109 families, with community jobs as traders, daily workers, self-employed, government employees and private employees. On average, only the husbands work, while the mothers are only housewives. The activities that are usually carried out by housewives are usually managing their yard, which is mostly planted with “jantan” bananas and kepok bananas, and only participating in PKK activities. So that the aim of the training in processing crispy bananas and coffee jam in the Simpang Kandis Region is to provide new skills in processing crispy bananas and coffee jam, attractive packaging and appropriate marketing. After this socialization and training, it can provide new skills to the PKK Women's Group in the Simpang Kandis RT 17 area regarding procedures for processing crispy bananas and coffee jam, simple packaging technology, and the right marketing strategy for crispy bananas and coffee jam